Formulasi dan Bioaktivitas Tetes Mata dari Ekstrak Air Bunga Telang (Clitoria ternatea L.) untuk Iritasi Mata - Michelle Audrey Teguh; Vania Uly Andyra; Irvine Eugenius Ignatio; Sendy Junedi (UIN Sunan Gunung Djati Bandung, 2023)
Eye irritation is a common ocular disease caused by blue light from gadgets and bacteria in air pollution. Long-term use of synthetic eye drops for treating antibacterial and antiinflammation may induce side effects. Clitoria ternatea flowers are empirically used to wash irritated eyes. The extract is known to have antiinflammation and antibacterial activity possibly because of anthocyanins and other types of flavonoids. By this research, the aqueous extract of Clitoria ternatea flower is formulated as eye drops, then tested for physicochemical, phytochemical, antiinflammation and antibacterial properties. Clitoria ternatea aqueous extract was prepared by maceration and formulated as eye drops with 0.025% w/v, 0.05% w/v and 0.1% w/v extract. All formulas were tested for physicochemical properties including pH, osmolarity and clarity, while phytochemical properties were flavonoid and anthocyanin content. Furthermore, antiinflammation activity was tested by inhibition of protein denaturation method, while antibacterial activity was tested against Staphylococcus aureus and Escherichia coli. Eye drops with 0.1% extract fulfilled physicochemical test including pH, osmolarity and clarity. Phytochemical test showed that 1 liter of 0.1% w/v eye drops contains 126.78 mg of flavonoids and 3.89 mg of anthocyanins. Eye drops showed higher antiinflammation activity than positive control with IC50 7.976 ppm. Meanwhile, 0.1% w/v (1,000 ppm) eye drops did not have antibacterial activity. However, increasing extract concentration to 50,000 ppm mg showed antibacterial activity. In conclusion, Clitoria ternatea flower aqueous extract can be used as eye drops to decrease common inflammation reaction due to blue light and other irritants.